RELATIONSHIP BETWEEN TREATMENT ADHERENCE AND PROGRESSION OF DIABETIC NEPHROPATHY - Chua, Jimmy; Firmansyah, Yohanes; Satyanegara, William Gilbert; Santoso, Alexander Halim; Su, Ernawati (Jurnal Muara Sains, Teknologi, Kedokteran dan Ilmu Kesehatan, 2021)
In 2006, the Indonesian Renal Registry (Pernefri) shows about 12,5% of people in Indonesia suffer from chronic kidney disease. The most common cause of chronic kidney disease in 2018 in Indonesia is 39% by renal hypertension and 22% by Diabetic Nephropathy. This cross-sectional study was conducted at "RT" Hospital in Jakarta from 2018 to 2019. The Independent variable in this research was comorbid hypertension and obedience treatment, whereas dependent variables were risk category for kidney deterioration progression and the causal relationship tested with Pearson Chi-Square and Fisher exact as an alternative test. The study included 26 respondents, with 17 (65.4%) patients having hypertension in diabetic nephropathy. Eighty percent of respondents who did not routinely seek treatment in the hypertension group had progression from kidney failure to the Deep Red (Highest Risk) category. Fisher Exact statistical test analysis in the group with a history of comorbidities in the form of hypertension found no significant relationship between non-routine treatment with the progression of chronic kidney failure in the Highest-Very Highest Risk category (p-value = 0.515). Still, a large risk was found in the non-group routine treatment with a chance of 1.33 (0.962 - 1.848) times to have the progression of chronic kidney failure in the category of Highest-Very Highest Risk. Can be concluded that controlling blood pressure and treatment proven to slow worsening kidney function in nephropathy diabetic, even though no significant relationship has been found due to lack of sample. Keywords: diabetic nephropathy; hypertension; prognosis AbstrakPerhimpunan Nefrologi Indonesia (Pernefri) tahun 2006 merilis data penderita gagal ginjal kronis di Indonesia sebesar 12,5%. Etiologi terbesar gagal ginjal kroniks menurut Indonesian Renal Registry tahun 2018 adalah penyakit ginjal hipertensi sebesar 39% dan nefropati diabetic sebesar 22%. Potong lintang pada pasien di RS”RT” Jakarta tahun 2018-2019. Variabel bebas dalam penelitian ini adalah komorbid hipertensi dan kepatuhan berobat, sedangkan variable tergantung dalam penelitian ini berupa kategori risiko progresifitas perburukan ginjal serta hubungan sebab akibat diuji dengan Peason Chi Square dan uji alternatif Fisher Exact Test. Penelitian berlangsung mengikutsertakan 26 responden, dengan prevalensi hipertensi pada pasien nefropati diabetik sebesar 17 (65,4%). Delapan puluh persen responden yang tidak rutin berobat pada kelompok hipertensi memiliki progresifitas penyakit gagal ginjal hingga kategori Deep Red (Highest Risk). Analisa uji statistik Fisher Exact pada kelompok dengan riwayat penyakit penyerta berupa hipertensi didapatkan tidak hubungan yang bermakna antara tidak rutin berobat dengan progresifitas penyakit gagal ginjal kronis kategori Highest-Very Highest Risk (p-value = 0,515) tetapi secara besar risiko didapatkan bahwa kelompok yang tidak rutin berobat memiliki risiko 1,33 (0,962 – 1,848) kali untuk memiliki progresifitas penyakit gagal ginjal kronis kategori Highest-Very Highest Risk. Dapat disimpulkan bahwa engontrol tekanan darah dan rutinitas berobat dapat memperlambat perburukan fungsi ginjal akibat komplikasi lanjut dari nefropati diabetikum, walaupun belum didapatkan hubungan yang bermakan dikarenakan kurangnya besar sampel pada penelitian ini.